2012
DOI: 10.11646/phytotaxa.50.1.3
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Fourteen new species and two taxonomic notes on Brazilian Myrtaceae</strong>

Abstract: Minas Gerais; Eugenia rotula was collected in rocky fields from the Bahian hinterland; Myrcia clavata and Myrciaria alagoana are from the Atlantic Rainforest of the northeastern state of Alagoas, and Myrcianthes riparia grows in riverine habitats in the highlands of the southern Brazilian states of Rio Grande do Sul and Santa Catarina. Additionally, there are proposed the rehabilitation of the name Eugenia astringens and the new name Myrcia neopauciflora, based on Aulomyrcia pauciflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Myrciaria tenella (cambuí) is a tree belonging to the Myrtaceae family, present in the Amazon, Caatinga, and Atlantic Forest biomes [12]. It has been verified that this species has anti-inflammatory, antimicrobial, and antimutagenic activities due to the presence of flavonoids, steroids, triterpenoids, and saponins [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Myrciaria tenella (cambuí) is a tree belonging to the Myrtaceae family, present in the Amazon, Caatinga, and Atlantic Forest biomes [12]. It has been verified that this species has anti-inflammatory, antimicrobial, and antimutagenic activities due to the presence of flavonoids, steroids, triterpenoids, and saponins [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is further worth mentioning that several new species were found in this region in the last two decades (Sommer & Ferrucci 2004;Lobão et al 2006;Sobral & Couto 2006;Fraga & Aymard 2007;Sobral et al 2012), with new distribution records (Menini Neto et al 2004;Almeida et al 2005;Matozinhos & Konno 2008;Versieux & Wendt 2006), and rare species for Minas Gerais state (Forzza et al 2014), also harboring Besleria brevicalyx G.E.Ferreira & Chautems (Gesneriaceae) (Ferreira et al 2016), endemic to the SR. Considering that 80% of the Atlantic Forest remnants have less than 50 ha (Ribeiro et al 2009), fragments having this extension can be considered rare and deserve attention.…”
Section: Resultsmentioning
confidence: 95%
“…Although Myrcianthes is closely related to the large genus Eugenia L. recent studies have confirmed its individuality and role as a sister group to the rest of the Eugenia clades [ 7 ]. Thanks to recent taxonomic research [ 8 , 9 ], new species belonging to the Myrcianthes genus have been described. Myrcianthes hallii (O. Berg) McVaugh is a medicinal and aromatic species commonly known in Ecuador as “arrayán” [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%